Određivanje ELISA-reaktivnih mumps IgG antitela kod primalaca MMR vakcine u poređenju sa decom koja nisu primila MMR vakcinu: studija preseka. - Gupta, Riya; Saxena, Naveen; Gupta, Parul (Scripta Medica, 2021)
Background/Aim: Mumps is by vaccine preventable infectious disease charac- terised by parotitis. In India mumps vaccines are not currently used under Na- tional Immunisation Programme (NIP). Waning of vaccine-induced immunity is considered to play a central role in the re-emergence of mumps. The compre- hensive data on the seroepidemiology of measles, mumps, and rubella (MMR) as well as studies which compare the antibody titre among mumps vaccine naive- and mumps vaccinated children are lacking. The aim of this study was to esti- mate and compare mumps specific antibody titre in children with and without MMR vaccine. Methods: In 2019/2020, blood samples were collected from 100 healthy chil- dren attending immunisation clinic in Government Medical College Kota and associated J K Lon Maternal and Child care hospital Kota. The samples were investigated for MMR IgG antibodies using ELISA. Results: Out of total 100 children included in the study, 32.27 % vaccinated and 4.83 % non-vaccinated children were positive for mumps IgG antibody in the age group of 6 months to 6 years of age. Children aged 6 to 12 years, vaccinat- ed and non-vaccinated, had 31.57 % and 26.57 % positivity, respectively. The seroprevalence of measles, mumps and rubella antibodies among 50 MMR vac- cinated children were 94 %, 64 %, and 96 %, respectively. A high measles and rubella seroprevalences were observed among all children age groups, suggest- ing an effective control program, while the mumps seroprevalence decreased significantly with age. Conclusion: The maximum vaccine effectiveness against mumps for 2 doses of MMR vaccine is ≈ 96 %. The herd immunity threshold to block mumps virus transmission is ≥ 86 %. In this study only 64 % of the vaccinated children were found to have IgG mumps antibodies. In view of morbidity following mumps infection there is a need to incorporate mumps vaccine along with measles and rubella vaccine in the NIP instead of MR.